2017
DOI: 10.1039/c7cc05974d
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective surface functionalization of lithographically designed gold nanorods by plasmon-mediated reduction of aryl diazonium salts

Abstract: Site-selective surface functionalization of anisotropic gold nanoparticles represents a major breakthrough for fully exploiting nanoparticle anisotropy. In this paper, we explore an original strategy for the regioselective functionalization of lithographically designed gold nanorods (AuNRs), based a combination of photo-induced plasmon excitation and aryl diazonium salt chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 27 publications
(17 reference statements)
1
37
0
Order By: Relevance
“…The SEM image and the extinction spectra of the substrate (Figs (a) and 3(b)) confirm that the AuNPs are covered by an organic layer (15–25 nm thick) which grows all around the NPs but also preferentially in the nanogaps between adjacent NPs. Similar growth (Figs (c) and 3(d)) was also observed around prolate NPs deposited by e‐beam lithography and reported in a recent publication with a different diazonium salt …”
Section: Plasmonic Electrochemistrysupporting
confidence: 88%
“…The SEM image and the extinction spectra of the substrate (Figs (a) and 3(b)) confirm that the AuNPs are covered by an organic layer (15–25 nm thick) which grows all around the NPs but also preferentially in the nanogaps between adjacent NPs. Similar growth (Figs (c) and 3(d)) was also observed around prolate NPs deposited by e‐beam lithography and reported in a recent publication with a different diazonium salt …”
Section: Plasmonic Electrochemistrysupporting
confidence: 88%
“…As grafting depends on the wavelength and polarization of the incident light, the orientation of the growth of the layer deposited on the AuNPs can be controlled. The mechanism of this plasmon‐induced deposition process is considered to be the transfer of hot electrons from the excited plasmonic NPs to the diazonium salt, triggering the subsequent chemical reactions leading to surface modification [66–68] …”
Section: Resultsmentioning
confidence: 99%
“…[65] Next TPP grafting from diazonium solutions was triggered by localized surface plasmons. Previous works have shown that oligo(bisthienylbenzene) (BTB) [66] and other aromatic units [67] can be deposited onto gold nanoparticles (AuNPs) or in the gaps between gold NP dimers [68] by visible-light illumination for a few minutes without any reducing agent or molecular photocatalyst. As grafting depends on the wavelength and polarization of the incident light, the orientation of the growth of the layer deposited on the AuNPs can be controlled.…”
Section: Electrochemical Characterization Of the Grafted Layersmentioning
confidence: 99%
See 1 more Smart Citation
“…Such localized effect can also be used for local photoinduced photoreactivity such as plasmon‐mediated functionalization and polymerization of analytes. To date this has been demonstrated in the visible region, however, such an approach could potentially be applied to mid‐infrared resonances using highly tunable quantum cascade lasers.…”
Section: Resultsmentioning
confidence: 99%